HHV8-Negative Primary Effusion Lymphoma of B-Cell Lineage: Two Cases and a Comprehensive Review of the Literature. (16th January 2013) - Saini, Neeraj; Hochberg, Ephraim P.; Linden, Erica A.; Jha, Smita; Grohs, Heinz K.; Sohani, Aliyah R.
Abstract : Primary effusion lymphoma (PEL) is a rare extranodal lymphoma that typically presents in a body cavity in the absence of a detectable tumor mass and that occurs predominantly in immunosuppressed individuals. The neoplastic lymphoid cells are frequently infected with human herpes virus 8 (HHV8), also known as Kaposi sarcoma herpes virus (KSHV). We describe two HIV-negative patients who presented with primary effusion lymphoma of B-cell lineage involving the pleural cavity, but whose tumor cells lacked infection by HHV8. We review the English language literature of HHV8-negative PEL of B-cell lineage and compare these lymphomas to HHV8-associated PEL with regard to clinical and pathological characteristics, therapy, and outcome.